Examining suspected dietary predictors of gestational hypertension in Iceland - Thinh Xuan Tran 1970- (2011)
The aim of this study was to investigate the association between few specific dietary factors such as fish, fish liver oil, coffee and tea during pregnancy and hypertensive disorders in pregnancy. The research questions that will be addressed is whether high consumption of fish or fish liver oil during pregnancy among Icelandic women can increase the risk of gestational hypertension; and if whether coffee or tea intake during pregnancy can reduce the risk of developing preeclampsia. A cohort of 491 pregnant Icelandic women who gave birth at landspitali National University Hospital, Reykjavik, Iceland in 1998. Women with pre-pregnant normal weight (BMI 19.5-25.5 kg/m2) were randomly selected from maternal records. The women were healthy before pregnancy, and had no history of hypertension, diabetes, cardiovascular disease, or thyroid problems. They were aged between 20-40 years old, and delivered singleton infants at 38.-43.week of gestation. Information on dietary intake was collected from maternal records by a food frequency questionnaire (FFQ). Maternity records gave information on maternal age, height, marital status, pre-pregnant weight, gestational weight gain, smoking and parity. Information on gestational hypertension and preeclampsia was diagnosed at the Department of Obstetrics and Gynecology, Landspitali National University Hospital. We used gestational hypertension is defined as systolic blood pressure (SBP) ≥ 140 mmHg and/or diastolic blood pressure (DBP) ≥ 90 mmHg on two or more occasions after 20 weeks of gestation, but without proteinuria as a primary outcome measure. Systolic and diastolic, isolated systolic, and isolated diastolic hypertension were used as secondary outcome measures. Preeclampsia was diagnosed as gestational hypertension and proteinuria of ≥ 0.3 g/24h or at least 1+ on a dipstick. In the first study we observed that the prevalence of gestational hypertension and preeclampsia was 102 (21%) and 15 (3%), respectively. Fish consumption was not associated with hypertensive disorders ...